BEHAVIORAL ECONOMICS AND EMPIRICAL PUBLIC POLICY1. Issue 1 (23rd January 2013) - Hursh, Steven R.; Roma, Peter G.
Abstract The application of economics principles to the analysis of behavior has yielded novel insights on value and choice across contexts ranging from laboratory animal research to clinical populations to national trends of global impact. Recent innovations in demand curve methods provide a credible means of quantitatively comparing qualitatively different reinforcers as well as quantifying the choice relations between concurrently available reinforcers. The potential of the behavioral economic approach to inform public policy is illustrated with examples from basic research, pre‐clinical behavioral pharmacology, and clinical drug abuse research as well as emerging applications to public transportation and social behavior. Behavioral Economics can serve as a broadly applicable conceptual, methodological, and analytical framework for the development and evaluation of empirical public policy.